Environmental Security in Transnational Contexts: What Relevance for Regional Human Security Regimes?. Issue 6 (1st November 2016) - Koff, Harlan; Maganda, Carmen
Abstract: The year 2015 was meant to be a seminal year in global geopolitics due to the transition from the Millennium Development Goals (MDGs) to the Sustainable Development Goals (SDGs). This transition was significant because the MDGs, even though they raised global consciousness around the need to combat poverty, remained indicator-based, and thus, they did not adequately address socio-economic inequalities and power imbalances in global affairs. For this reason, much of the discussion surrounding the definition of the SDGs and the post-2015 global development agenda contextualized sustainable development within the framework of 'transformation', specifically prioritizing concepts such as equity, security, justice, and rights. While these debates correctly discussed power imbalances and relational obstacles to human development they remained abstract because they focused only on the international level. In this regard, discussions did not adequately examine mechanisms that facilitate or block the emergence of sustainable development as a political priority, nor did they address specific policy proposals to link environmental justice to human development strategies. Thus, this special issue introduction argues that human and environmental security should be framed in terms of transnational discussions rather than being limited to international debates. The special issue undertakes an examination of the interactions between human and environmental security, border studies, and comparative regional integration; and interactions between competing globalizations. The articles in the special issue address the relationships between international norms, transnational human and environmental security issues, and the regionalization of governance.